Measures for Realizing “The MIDORI Strategy” and Promoting Organic Farming - Matsumoto, Yoshihide (Journal of Rural Problems, 2025)
Activities in agriculture, forestry and fisheries are making negative impacts on the environment in general. To mitigate these impacts, some environmental policies are being enforced in USA, EU and other developed countries. Against this background Ministry of Agriculture, Forestry and Fisheries had implemented the policy of “The MIDORI Strategy” on May, 2021. Current status of organic farming in Japan is far from the goal of “The MIDORI Strategy”. It aims to have 1,000,000ha equipped with organic agricultural techniques, which can be 25% of total arable land in Japan. This strategy has 14 key performance indicators. These indicators are closely related with recent geopolitical risks, which make the market prices of chemical fertilizers, chemical pesticides and some other inputs required by conventional agricultural techniques. Organic agricultural techniques have labor-using technical characteristics. Both the development of suitable technologies made by R & D and the dissemination support made by policy and extension stations must be required in order to overcome these characteristics and dramatically enhance organic farming in Japan.